Environmental Study On Co2 Storage In The Deep Sea: An Overview - M.S Wibisono; Hanifah Iswandari (Testing Center for Oil and Gas LEMIGAS, 2011)
Global warming is an important environmental issue caused by the accumulation of CO2 in the atmosphere that may result in climate change with several impacts. Such gas must be reduced by various ways of action from cross-sectoral human activities including scrapping or sequestration technique. The gas can be delivered by pipes or tanker ship following the sequestration to be stored by injecting method. One of the proposed storage sites for such gas which still in the scientific polemic is in the deep sea. he problems appeared such as the overall processes are considered as a high cost technology for the developing countries excluding additional energy cost. Furthermore the basic legal system to regulate and to control the activity is not yet provided in Indonesia. This paper presents a short discussion from several aspects with the aim to obtain problem solving if such gas would be stored in the deep sea. It is also suggested from the scientific point of view that profound study on CO2 storage should be undertaken from laboratory scale as well as in the deep sea. Since the chemical-based scrapping or sequestration of CO2 and its storage need high cost investment and operation, so at least the biological-based sequestration combined with environmental oriented physical-chemical based are offered.